Effectiveness of Organizing a Non-Face to Face Tutorial Package System in Distance Education - Budiastra, A.A. Ketut; Kusmawan, Udan; Hanafi (Advances in Social Sciences Research Journal, 2020)
At this time, the number of students of elementary school teacher programs at the Universitas Terbuka (UT) in one study group as many as 20-30 people in some places there is a tendency challenging to be fulfilled. This challenge because most elementary school teachers already have a bachelor’s degree. Meanwhile, the location of students at this time tends to be increasingly scattered with distant geographical areas, so it is necessary to provide a particular service called the Non-Face to Face Tutorial Package System (NFFTPS) for Practical/Practicum courses. The sample in this study was the undergraduate students of elementary school teacher programs in the regional office of Pangkalpinang, Serang, Bandung, Denpasar, Ambon, amounting to 75 respondents. This research is categorized as a qualitative descriptive study. From the results of this study, it can be concluded that the NFFTPS program has been implemented quite well. However, in its implementation, there are still many obstacles encountered and need to be refined in the future. Besides, there is a need for a synergy of academic guidance services for NFFTPS programs in regional office and UT central so that they can provide quality, appropriate, timely, and targeted services.